Emergency and Disaster Management in the Health Sector - Yusanda, Carissa Aprilia; Sidharti, Liana (CV. Jasa Sukses Abadi, 2024)
In this era of globalization, humans are faced with various challenges, including threats from disasters and emergency situations that can harm the health sector. Emergency and disaster management in the health sector is a critical aspect that requires serious attention. The importance of emergency and disaster management in the health sector is not only related to handling individual cases, but also involves prevention, preparedness and recovery efforts. The absence of adequate preparation can have serious impacts on public health, threaten the resilience of health systems, and increase the risk of disease. By adopting a qualitative approach, this research uses a case study design to gain an in-depth understanding of practices and policies related to preparedness, response and recovery in health emergencies. Through an in-depth understanding of emergency and disaster management in the health sector, it is hoped that innovative and effective solutions can be found in facing complex challenges that arise from natural disasters, armed conflicts, or global health threats. This research is expected to provide a valuable contribution to the development of policy, practice and advanced research in the field of emergency and disaster management that focuses on health aspects. The research findings highlight significant variations in the level of health system preparedness across contexts. The active involvement of stakeholders, including governments, non-governmental organizations and local communities, is identified as a key factor in successful emergency management. Environmental factors, such as geography and social dynamics, also influence the strategies implemented to respond to and recover from the health impacts of disasters.